Adolescent Isolation Interacts With DISC1 Point Mutation to Impair Adult Social Memory and Synaptic Functions in the Hippocampus - Li, Nan; Cui, Lin; Song, Ge; Guo, Li; Gu, Huating; Cao, Haisheng; Li, Guo-Dong; Zhou, Yu (Frontiers in Cellular Neuroscience, 2018)
Disrupted-in-schizophrenia 1 (DISC1) is a strong candidate susceptibility gene for a spectrum of neuropsychiatric diseases including schizophrenia, bipolar disorder and major depression, all of which are thought to result from interactions between gene mutations and environmental risk factors such as influenza, trauma and stress. Adolescence is a key period susceptible to stress and stress-related mental illnesses. In a previous study, we found that although DISC1 L100P point mutation mice shows object recognition deficits, their sociability and social memory are relatively normal. Therefore, in this paper, we investigated whether the interaction between adolescent stress and DISC1 L100P point mutation affects adult social memory, and we explored the underlying mechanisms. We found that adolescent stress (isolation from 5-8 weeks of age) specifically impaired social memory of adult DISC1 L100P mice but not that of WT littermates, which could be rescued by administration of atypical antipsychotic drug clozapine. On the other hand, it did not induce anxiety or depression in adult mice. Adolescent isolation exacerbated adult neurogenesis deficits in the hippocampus of DISC1 L100P mice, while it had no effect on WT mice. In addition, we found that adolescent isolation led to long lasting changes in synaptic transmission and plasticity in the hippocampal circuits, some of which are specific for DISC1 L100P mice. In summary, we identified here the specific interaction between genetic mutation (DISC1 L100P) and adolescence social stress that damages synaptic function and social memory in adult hippocampal circuits.